2002
DOI: 10.1023/a:1015234318582
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity of Breast Cancer Patients Following Complete Axillary Dissection or Sentinel Node Biopsy Only: A Comparative Evaluation

Abstract: SNB appears to be an accurate procedure for axillary nodal staging in breast cancer patients and is associated with reduced postoperative morbidity and length of hospital stay. But it is still investigational and should not be implemented as therapeutical standard before results of randomized trials are published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
77
3
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 13 publications
8
77
3
5
Order By: Relevance
“…The present study confirms previous observations suggesting that SLNB is associated with less arm/shoulder morbidity (Giuliano et al, 2000;Schrenk et al, 2000;Burak et al, 2002;Haid et al, 2002;Temple et al, 2002) than ALND. Evaluation and comparison of QOL outcomes in a short time follow-up in breast cancer patients undergoing ALND or SLNB after breast-conserving surgery provides additional observations:…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study confirms previous observations suggesting that SLNB is associated with less arm/shoulder morbidity (Giuliano et al, 2000;Schrenk et al, 2000;Burak et al, 2002;Haid et al, 2002;Temple et al, 2002) than ALND. Evaluation and comparison of QOL outcomes in a short time follow-up in breast cancer patients undergoing ALND or SLNB after breast-conserving surgery provides additional observations:…”
Section: Discussionsupporting
confidence: 92%
“…These results support the hypothesis, that current standard questionnaires do not cover all aspects of QOL (Janni et al, 2001). Several aspects of morbidity including pain, range of motion and sensory complaints of the affected arm have been reported to show significant difference in favour of SLNB (Giuliano et al, 2000;Schrenk et al, 2000;Burak et al, 2002;Haid et al, 2002;Temple et al, 2002). However, measuring instruments and scoring systems used in these studies differ widely.…”
Section: Discussionsupporting
confidence: 76%
“…[9][10][11] An increasing number of studies reported EJSO 32 (2006) less treatment related morbidity for SLNB in comparison to ALND. [12][13][14][15][16][17][18][19][20] Generally disability in ADL of the SLNB group was less than that of the ALND group. 13,16,19 A shortcoming in most studies is the absence of pretreatment assessment and the absent of reliable and validated assessment instruments.…”
Section: Introductionmentioning
confidence: 89%
“…However, it is associated with significant morbidity, including postoperative arm lymphedema and neuropathy of the involved extremity, and seroma formation in the axilla (Noguchi et al, 1997). Particularly, arm lymphedema develops in 7%-77% of patients who undergo axillary lymph node dissection (Blanchard et al, 2003;Leidenius et al, 2005;Haid et al, 2002;Mansel et al, 2006;Ronka et al, 2005;Schijven et al, 2003;Schrenk et al, 2000;Swenson et al, 2002). At present, sentinel lymph node biopsy is accepted as the standard method of surgical staging for axillary lymph nodes in breast cancer.…”
Section: Introductionmentioning
confidence: 99%